Exploration of Using the PADLET App in Teaching Writing at State Senior High Schools - Budiyanto, Darmawan; Tridinanti, Gaya; Ridho, M.Rasyid (International Journal of Education Research and Development, 2025)
This study investigates how Palembang senior high school students may improve their writing abilities by using the PADLET software. The research combines quantitative and qualitative analysis using a mixed-methods methodology. A quasi-experimental method is used for the quantitative component, using purposive sampling with 120 students from four different schools split into experimental and control groups. While the control groups used conventional techniques, the experimental groups used PADLET for writing exercises. Writing performance gains were measured using pre- and post-tests. Qualitative data were gathered through interviews with eight English teachers to understand their experiences with PADLET in the classroom. Statistical analysis of writing scores showed significant improvements in the experimental groups. Thematic analysis of teacher interviews revealed positive perceptions of PADLET, highlighting its potential to boost collaboration and student engagement. The study concludes that PADLET is an effective tool for teaching writing, offering both educational and practical benefits.